Modificação superficial por fricção e agitação nas ligas de alumínio Al12Si e Al14Si - Traiano, Denner (2023)
The increasing demand for technological solutions that promote improvements in materials and their properties of interest is a subject of intensive research in the engineering sectors. Thus, the necessity of developing surface modification processes aimed at enhancing the surface characteristics of materials is increasingly studied and applied. The surface modification of aluminum alloys has become appealing due to new possibilities for applications and property development. In this context, the utilization of the Friction Stir Processing (FSP) technique emerges as a key resource for the surface modification of cast aluminum alloys. This present dissertation aims to analyze the influence of the friction and agitation process on changes in microstructure, microhardness, as well as wear and corrosion resistances in Al12Si and Al14Si alloys. The methodology was devised for conducting experiments involving the combination of the following process parameters (n and vf): 700 rpm at 16 mm/min, 850 rpm at 22 mm/min, and 1100 rpm at 28 mm/min. Within the conducted experimental process, evaluations and analyses of corrosion resistance, wear resistance, and microhardness were carried out, with cross-sectional and surface profiles of the samples being obtained. Statistical methods such as Analysis of Variance (ANOVA) and the Response Surface Method (RSM) were employed. The analyses, which incorporated data from X-ray Fluorescence (XRF) for chemical composition and images from Optical Microscopy (OM) and Scanning Electron Microscopy (SEM), facilitated the examination of regions formed by the friction and agitation process, namely the HeatAffected Zone (HAZ), the Thermomechanically Affected Zone (TMAZ), and the core region. It was observed that in the core region, there was fragmentation and homogenization of second-phase particles such as iron AlFeMnSi-Fe- and AlFeSiFe-, copper Al2Cu-, and silicon particles, leading to the homogenization and distribution of these particles. Distinct outcomes were recorded in each alloy concerning the parameters used for surface modification. For Al12Si alloy, the condition of 700 rpm at 16 mm/min resulted in an approximate 23% increase in microhardness compared to the base metal. Additionally, a 24% reduction in the Coefficient of Friction (COF) was noted, alongside reports of smaller silicon particle sizes and reduced iron and copper intermetallic sizes. Conversely, the condition of 850 rpm at 22 mm/min yielded the highest annual corrosion resistance when compared to the base metal Al12Si, leading to a reduction of around 79% in the annual corrosion rate. For the Al14Si alloy, the condition of 700 rpm at 16 mm/min resulted in a 30.2% increase in microhardness and a 72% reduction in corrosion rate compared to the base metal. However, for friction coefficient analyses, the condition of 1100 rpm at 28 mm/min exhibited a 21% reduction in friction rate. With a 95% reliability, statistical methodologies demonstrated that the optimal alloy for developing the surface modification process is Al12Si, paired with the 700 rpm at 16 mm/min parameter. The Friction Stir Processing technique yielded improved results in microstructure, microhardness, wear resistance, and corrosion resistance across all modification conditions.